Manual de Procedimientos Administrativo, Contable y Tributario en la Empresa Distribuciones San Blass de La Ciudad de Loja, Período 2021. - Soto Soto, Isidro Eliazar (2023)
The present Curricular Integration work, "Manual of Administrative, Accounting, and Tax Procedures in the Company Distribuciones San Blass of the City of Loja, Period 2021", contains an investigation focused on analyzing the administrative, accounting, and tax fields of the company with the purpose of the correct development of the functions and activities that are carried out daily to guide and manage its business operations, strategies, and workflows towards optimal results, as well as maintaining quality and efficiency standards. For the development of this research work, an interview was conducted with the owner- manager of Distribuciones San Blass, based on a questionnaire of questions allowing for the acquisition of relevant information, proposing a SWOT analysis where the strengths, weaknesses, opportunities, threats, and situation of the company were determined, obtaining a diagnosis that allowed us to know the current situation in which the company is located. Subsequently, the administrative, accounting, and tax activities were detailed in order to establish the necessary procedures, structured by objectives, scope, responsibilities, and policies. In the administrative field, a structural and functional organization chart was developed and proposed for its application to the entity, Procedures focused on personnel such as recruitment and selection, training, permits, licenses, vacations, and attendance control. In the accounting part, a plan and manual of accounts, source documentation and standard entries were designed to serve as a guide for daily transactions, inventory acquisition, opening, counting and closing of cash, bank reconciliation, depreciation of property, plant and equipment, payment of wages and salaries, for the tax field, procedures were developed on the tax obligations that the company has, with the sole purpose that the entity knows about the taxes that they are obliged to declare and the annexes to be used according to current regulations to avoid the respective fines and penalties Finally, flowcharts were designed for each procedure in the administrative, accounting, and tax part that will allow following the steps of a process, and easily identify the activities to be carried out in order to achieve greater efficiency and effectiveness in the execution of the tasks and contribute to obtaining of the detailed and ordered information assigned to the personnel that works in Distribuciones San Blass.